2014
DOI: 10.4049/jimmunol.1401184
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Release of CCL5 Storage Vesicles Triggers CXCR4 Surface Expression Promoting CTL Migration in Response to CXCL12

Abstract: The lytic function of CTL relies on the polarized release of cytotoxic granules (CG) at the immune synapse (IS) with target cells. CTL also contain CCL5 in cytoplasmic storage vesicles (CCL5V) distinct from CG, the role of which, in regulating T cell effector functions, is not understood. Using human CD8+ T cells specific to a lung tumor–associated Ag, we show in this article that CTL release both secretory compartments into the immune synapse with autologous tumor cells. Moreover, we demonstrate that disorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
4
9
1
Order By: Relevance
“…an early (2h) association of intracellular chemokine stores with the IS followed by a later (4h) distribution in multiple compartments throughout the cytoplasm [76]. In agreement with the latter report, however, we found that p14 TE on occasion presented low amounts of antipolar surface CCL5 ( Fig.7C, panel 6) and it is tempting to speculate that the heterogenous subcellular distribution of pre-stored CCL5 is related to the reported association with distinct trafficking proteins that mediate a multidirectional vs. focused chemokine release [75,76].…”
Section: Rapid Ccl5 Surface Translocation and Secretion By Virus-specsupporting
confidence: 91%
See 1 more Smart Citation
“…an early (2h) association of intracellular chemokine stores with the IS followed by a later (4h) distribution in multiple compartments throughout the cytoplasm [76]. In agreement with the latter report, however, we found that p14 TE on occasion presented low amounts of antipolar surface CCL5 ( Fig.7C, panel 6) and it is tempting to speculate that the heterogenous subcellular distribution of pre-stored CCL5 is related to the reported association with distinct trafficking proteins that mediate a multidirectional vs. focused chemokine release [75,76].…”
Section: Rapid Ccl5 Surface Translocation and Secretion By Virus-specsupporting
confidence: 91%
“…In order to better visualize the earliest events of TCR-induced CCL5 release, we performed an in vitro conjugation assay using purified p14 TE (CD90.1) and congenic (CD90.2) GP33 peptide-coated vs. Our data therefore support the notion that mobilization of intracellular CCL5 stores is primarily directed towards the IS similar to the polarization reported for polyclonally activated human CD8 + T cell blasts and clones [65,75]; yet they apparently differ from results of another study in which the de novo synthesis of CCL5 by in vitro generated murine CD4 + T cell blasts resulted in multidirectional release of this chemokine, i.e. an early (2h) association of intracellular chemokine stores with the IS followed by a later (4h) distribution in multiple compartments throughout the cytoplasm [76].…”
Section: Rapid Ccl5 Surface Translocation and Secretion By Virus-specsupporting
confidence: 71%
“…On the contrary, we identified a decrease in the expression of chemokine (C-C motif) ligand 5 ( Ccl5 ) and Cxcl12 in KL tumor cells as compared to Kras . Both of these chemokines play an important role in recruiting lymphocytes and dendritic cells (20,21) and these cell types are underrepresented in KL tumors (Supplementary Fig. S1C and D).…”
Section: Resultsmentioning
confidence: 99%
“…For example, although tumor derived CXCL12 has been reported to attract T cells (30), (31) it also exerts important tumor-promoting functions. In fact, CXCL12 and CXCL16 are overexpressed in epithelial ovarian carcinomas (32, 33), and other solid tumors (34, 35).…”
Section: Discussionmentioning
confidence: 99%